1993
DOI: 10.2134/jeq1993.00472425002200030002x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Nitrate in Groundwater—A Review

Abstract: The results of federal, state, and local surveys, which included more than 200 000 NO3‐N data points, are summarized in this review of NO3 in groundwater in the USA. The levels of NO3‐N are associated with source availability and regional environmental factors. In regions where well‐drained soils are dominated by irrigated cropland, there is a strong propensity toward the development of large areas with groundwater that exceeds the maximum contaminant level of 10 mg/L NO3‐N. Most of these areas are west of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
461
0
8

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 946 publications
(496 citation statements)
references
References 0 publications
12
461
0
8
Order By: Relevance
“…Poorly managed agricultural operations can lead to contamination of surface water and groundwater by nutrients and pesticides (Spalding and Exner 1993;Pereira et al 1996;Kolpin et al 1998;Novotny 1999;Gunningham and Sinclair 2005). Periodic use of these products in agriculture will cause dispersion within the environment by means of drift, run-off and drainage (Kolpin et al 1998;Guzzella et al 2006;Papastergiou and Papadopoulou-M 2001).…”
Section: Pesticidesmentioning
confidence: 99%
“…Poorly managed agricultural operations can lead to contamination of surface water and groundwater by nutrients and pesticides (Spalding and Exner 1993;Pereira et al 1996;Kolpin et al 1998;Novotny 1999;Gunningham and Sinclair 2005). Periodic use of these products in agriculture will cause dispersion within the environment by means of drift, run-off and drainage (Kolpin et al 1998;Guzzella et al 2006;Papastergiou and Papadopoulou-M 2001).…”
Section: Pesticidesmentioning
confidence: 99%
“…Nitrate occurrence and transport in aquifers have been widely studied since it is one of the 39 major threats in groundwater, and most aquifers in agricultural areas are affected by this 40 contaminant (Spalding and Exner, 1993;EEA, 2012). Most of the papers that focused on 41 nitrate pollution study, by means of hydrochemical and isotopic data, nitrate trends in 42 groundwater at different scales to identify potential sources of pollution and build-up 43 hydrogeochemical models to understand the behavior of nitrate polluted aquifers (for 44 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 reported that the concentration of some major inorganic components in pig manure, the most 64 used organic fertilizer in the studied areas in Catalonia (NE Spain), is notably larger than 65 their natural values in groundwater.…”
Section: Introduction 38mentioning
confidence: 99%
“…Also, the World Health Organization (WHO) indicates a guideline value (GV) of 50 mg/l for drinking water (WHO 2004), which has been integrated into Italian national law as a MAC. A high nitrate concentration is always related to anthropogenic contamination, the main sources being fertilizers and human or animal bodily waste (Spalding and Exner 1993). Nitrate can be the main anionic species in both agricultural and urban areas.…”
Section: Introductionmentioning
confidence: 99%